Infiltration of tumor‐associated macrophages is involved in tumor programmed death‐ligand 1 expression in early lung adenocarcinoma. Issue 2 (6th January 2020) - Shima, Toshiyuki; Shimoda, Masayuki; Shigenobu, Takao; Ohtsuka, Takashi; Nishimura, Tomoyasu; Emoto, Katsura; Hayashi, Yuichiro; Iwasaki, Tatsuro; Abe, Takayuki; Asamura, Hisao; Kanai, Yae
Abstract: Programmed death‐ligand 1 (PD‐L1) is an immune modulator that promotes immunosuppression by binding to programmed death‐1 of T‐lymphocytes. Although tumor cell PD‐L1 expression has been shown to be associated with the clinical response to anti–PD‐L1 antibodies, its concise regulatory mechanisms remain elusive. In this study, we evaluated the associations of tumor PD‐L1 expression and immune cell infiltrating patterns in 146 cases of early lung adenocarcinoma (AC) to investigate the possible extrinsic regulation of tumor PD‐L1 by immune cells. Using immunohistochemistry, cell surface PD‐L1 expression in tumor cells was observed in 18.5% of stage 0‐IA lung AC patients. Tumor PD‐L1 positivity was significantly associated with stromal invasion, which was accompanied by increased tumor‐associated macrophages (TAM), CD8 + cytotoxic T cells and FoxP3 + regulatory T cells. Among these immune cells, TAM and CD8 + T cells significantly accumulated in PD‐L1‐positive carcinoma cell areas, which showed a tumor cell nest‐infiltrating pattern. Although CD8 + T cells are known to induce tumor PD‐L1 expression via interferon‐ɣ production, the increased TAM within tumors were also associated with tumor cell PD‐L1 positivity, independently of CD8 + T cell infiltration. Our in vitro experiments revealed that PD‐L1 expression in lung cancer cell lines was significantly upregulated by co–culture with M2‐differentiated macrophages; expression of PD‐L1 was reduced to baseline levels following treatment with a transforming growth factor‐β inhibitor. These results demonstrated that tumor‐infiltrating TAM are extrinsic regulators of tumor PD‐L1 expression, indicating that combination therapy targeting both tumor PD‐L1 and stromal TAM might be a possible strategy for effective treatment of lung cancer. Abstract : In this study, we showed that tumor‐associated macrophage (TAM) infiltration was an additional factor related to tumor programmed death‐ligand 1 (PD‐L1) expression in early lung adenocarcinoma. Our in vitro experiments demonstrated that M2‐differentiated macrophages facilitated tumor PD‐L1 expression through transforming growth factor‐β. These results suggested that TAM were extrinsic regulators of tumor PD‐L1 expression and could serve as potential therapeutic targets.